The Cytochrome P450 Gene CsCYP85A1 Is a Putative Candidate for Super Compact-1 (Scp-1) Plant Architecture Mutation in Cucumber (Cucumis sativus L.) - Wang, Hui; Li, Wanqing; Qin, Yaguang; Pan, Yupeng; Wang, Xiaofeng; Weng, Yiqun; Chen, Peng; Li, Yuhong (Frontiers in Plant Science, 2017)
The dwarf or compact plant architecture is an important trait in plant breeding. A number of genes controlling plant height have been cloned and functionally characterized which often involve in biosynthesis or signaling of plant hormones such as brassinosteroids (BRs). No genes for plant height or vine length have been cloned in cucurbit crops (family Cucurbitaceae). From an EMS-induced mutagenesis population, we identified a super compact (SCP) mutant C257 which was extremely dwarf due to practically no internode elongation. Under dark growing condition, C257 did not undergo skotomorphogenesis and its mutant phenotype could be rescued with exogenous application of brassinolide, suggesting SCP might be a BR-deficient mutant. Segregation analysis revealed a single recessive gene scp-1 that was responsible for the SCP mutation. Map-based cloning combined with a modified MutMap identified CsCYP85A1, a member of the plant cytochrome P450 monooxygenase gene family, as the most possible candidate gene for scp-1, which encodes a BR-C6-oxidase in the BR biosynthesis pathway. We show that a SNP within the second exon of scp-1 candidate gene caused the SCP phenotype. Three copies of the CsCYP85A gene are present in the cucumber genome, but only the scp-1/CsCYP85A1 gene seemed active. The expression of CsCYP85A1 was higher in flowers than in the leaves and stem; its expression in the wild type was feedback regulated by brassinolide application. Its expression was reduced in C257 as compared with the wild type. This was the first report of map-based cloning of a plant height gene in cucurbit crops. The research highlighted the combined use of linkage mapping, an improved MutMap method and allelic diversity analysis in natural populations in quick cloning of simply inherited genes in cucumber. The roles of CsCYP85A1 in regulation of internode elongation in cucumber was discussed.